On the Validation of Gyrokinetic L-Mode Simulations. (1st April 2016) - Görler, T.; White, A. E.; Told, D.; Jenko, F.; Holland, C.; Rhodes, T. L.
Abstract: Over the last decade, plasma turbulence simulations based on gyrokinetic theory have reached an amazing degree of physical comprehensiveness and realism. In contrast to early gyrokinetic studies, which were restricted to qualitative statements, state-of-the-art investigations may now be compared quantitatively, therefore enabling validation and detailed analysis of their predictive capabilities. Here, particular attention is paid to outer-core L-mode discharges for which some previous gyrokinetic studies have found an underprediction of ion heat transport by almost one order of magnitude, the so-called shortfall. Carrying out radially local and nonlocal GENE simulations using actual plasma profiles and parameters and magnetohydrodynamic equilibria, and employing as much physics as available, only a mild underprediction is found, which can, furthermore, be overcome by varying the ion temperature gradient within the error bars associated with the experimental measurement. The significance and reliability of these simulations is furthermore demonstrated by extensive comparison with experimental measurements. The latter involve sophisticated synthetic beam emission spectroscopy and correlation electron cyclotron emission data analysis. The agreement found between the measurements and the state-of-the-art postprocessed simulation data confirms the high degree of realism.